Implementation of Hy-Bon Edugame Based on Gender of Students' Learning Interest In Hydrocarbon - Rokhim, Deni Ainur; Nora, Nora; Sari, Anggreani Puspita; Rokayah, Dede Yayah (Universitas Negeri Malang, 2022)
This research is geared toward observational data, which aims to determine the increase in the interest in learning of male and female gender students in science material, especially low CHEMISTRY. The objectives to be achieved in this research are to determine the implementation of the quasi-experimental method of